DINAMIKA PARTAI POLITIK ISLAM DALAM PEMBENTUKAN PERATURAN DAERAH BERNUANSA ISLAMI DI KABUPATEN ASAHAN - Syam, Syafruddin; Zaleha, Zaleha; ZR, Surono (Universitas Al-Amien Prenduan, 2023)
This research article aims to find out the dynamics of Islamic political parties with Islamic nuances in Asahan Regency providing arguments and subangsih in Islamic nuanced bylaws in Asahan Regency. Data input and collection are carried out by direct involvement and interviews (Indeepth Interview), direct observation with a sampling method that is carried out deliberately (Purposive sampling), the approach implemented is symbolic interaction. The result of this research is to state that in responding to, analyzing and participating in summarizing regional regulations with Islamic nuances in Asahan Regency, be more vigilant so that there are no clashes with other groups. It started when the Islamic party in Asahan Regency analyzed the